Cellular Therapy with Autologous Mesenchymal Stromal Cells in Patients with Drug Resistant Pulmonary Tuberculosis - V. V. Solodovnikova; A. E. Skryagin; Y. I. Isaykina; D. A. Klimuk; G. L. Gurevich; E. M. Skryagina (Туберкулез и болезни лёгких)
The objective: to evaluate the effectiveness of treatment with autologous mesenchymal stromal cells (MSCs) in patients with drug resistant pulmonary tuberculosis (DR TB).Subjects and Methods. 120 patients with drug resistant tuberculosis aged 18 to 61 years old were enrolled in the study. They all were treated at the Republican Scientific and Practical Center of Pulmonology and Phthisiology from 2009 to 2018. Against the background of anti-tuberculosis treatment, patients (60 people) from Main Group (MG) underwent bone marrow sampling and then intravenous administration of autologous MSCs.Results. The average dose of administered cells was 1x106 per kg of the patient body weight. The average duration of MSC cultivation made 35 days. Treatment effectiveness in MG made 90% versus 71% in Control Group (CG). All patients who were successfully cured of tuberculosis (TB) using autologous MSCs had no tuberculosis relapses during 5 years of follow-up. In Control Group, 8 (19%) cases of relapse were reported. In Main Group versus Comparison Group, the rates indicating healing of cavities and absence of relapse are statistically significantly better.Conclusion. The use of autologous MSCs in patients with drug resistant tuberculosis has shown its high effectiveness.